EDUKASI MANFAAT PEMERIKSAAN GOLONGAN DARAH DAN BANK DARAH DESA (BDD) BETUNG I - Apriyani Apriyani (IKesT Muhammadiyah Palembang, 2022)
Individual blood type is important to know, this is related to clinical importance. If a person requires medical action related to blood transfusion, it is important to know the individual's blood type to avoid a transfusion reaction. Human blood types are generally divided into blood groups A, B, AB, O and Rh. The purpose of this community service is to find out the blood type of the community in Betung I Village by using leaflet media. This community service activity was attended by 35 respondents. Results and Conclusions is to be able to know the blood type you have so that if at any time there is an emergency that requires a blood transfusion, it can be handled immediately.